Disk Galaxies in the Magneticum Pathfinder Simulations. Issue Volume 10:Issue S309(2014) (9th February 2015) - Remus, Rhea-Silvia; Dolag, Klaus; Bachmann, Lisa K.; Beck, Alexander M.; Burkert, Andreas; Hirschmann, Michaela; Teklu, Adelheid
Abstract: We present Magneticum Pathfinder, a new set of hydrodynamical cosmological simulations covering a large range of cosmological scales. Among the important physical processes included in the simulations are the chemical and thermodynamical evolution of the diffuse gas as well as the evolution of stars and black holes and the corresponding feedback channels. In the high resolution boxes aimed at studies of galaxy formation and evolution, populations of both disk and spheroidal galaxies are self-consistently reproduced. These galaxy populations match the observed stellar mass function and show the same trends for disks and spheroids in the mass–size relation as observations from the SDSS. Additionally, we demonstrate that the simulated galaxies successfully reproduce the observed specific angular-momentum–mass relations for the two different morphological types of galaxies. In summary, the Magneticum Pathfinder simulations are a valuable tool for studying the assembly of cosmic and galactic structures in the universe.